Política e teocentrismo em A Rainha Santa e A Rainha Vermelha: a representação feminina em perspectiva - Pontes, Francisco Edinaldo de (2022)
This Dissertation aims to do a comparative analysis of the protagonists of two novels, in the domains of the Iberian Peninsula and Anglo-Saxon, Lady Isabel of Aragon and Lady Margaret Beaufort, investigating, in this way, the feminine representation and its power relations in a political perspective – under the bias of Political Feminism (1970) – in a theocentric context in the portuguese contemporary historical novel The Saint Queen (2017) by Isabel Machado and in the english contemporary historical novel The Red Queen (2019) by Philippa Gregory. As thesis-idea, we have assumed that Lady Isabel of Aragon and Lady Margaret Beaufort use the religion and the theocentric dominion of the Late Middle Age as a way to realize their diplomatic activities and to impose theirselves in a political way. Both use their reputation of Agnes and Agnus Dei as political strategies in the portuguese and english kingdoms in a highly religious historical setting. Thus, the present work is justified by the need, through the new historical novel, to revisit, in the scope of Literature and History, the great deeds, diplomatic, and political transgressions, as well as the contributions of these women to the politics-historical evolution of portuguese and english medieval European civilization. As a methodological forwarding, the present essay consists of an explicative research with a bibliographical slant and with a textual interpretation approach, remiting itself to the inductive method. We have used as the main instrument of analyzing of the protagonists the study of a structuralist and comparative nature. For the theoretical basis of our research, we have relied on, amongst others, the studies by Castor (2012); Duby e Perrot (1990); Hutcheon (1991); Klapisch-Zuber (1990); Le Goff (2005a, 2005b); L’HermiteLeclercq (1990); Marinho (1999); Millett (1968, 1970); Muraro (2002); Opitz (1990); Perrot (2017); Woolf (2014, 2019); Vieira (2000); Zinani (2011a, 2011b, 2014); Zolin (2009a, 2009b, 2010, 2012). In short, we have noticed that, Lady Isabel of Aragon and Lady Margaret Beaufort achieved the most part of their political goals as sovereigns in a total patriarchal context; in other words, they reigned and ruled in a time in which it was not expect that women acted into public sphere, even more, into the ambit of the political power, justifying, thus, their epithets of The She-Wolves: The Reginas.